Evaluation of the Kappaphycus alvarezii growth under different environmental conditions and efficiency of the enzymatic hydrolysis of the residue generated in the carrageenan processing - Solorzano-Chavez, Eddyn Gabriel [UNESP]; Paz-Cedeno, Fernando Roberto [UNESP]; Ezequiel de Oliveira, Levi; Gelli, Valéria Cress; Monti, Rubens [UNESP]; Conceição de Oliveira, Samuel [UNESP]; Masarin, Fernando [UNESP] (Elsevier, 2019)
Kappaphycus alvarezii is a red macroalgae generally used for industrial production of hydrocolloids. An alternative is to use the K. alvarezii for carrageenan production and its residue for the manufacture of bioproducts of commercial interest (biofuels, food, cosmetics, nutraceuticals, pharmaceuticals, and biofertilizers). This study reported the cultivation of K. alvarezii strains in different environmental conditions over a period of one year. The productivity, growth rate, and yield of refined carrageenan (RC) and residue (RE) of the studied crops were evaluated. Moreover, the efficiency of the enzymatic hydrolysis of the RE obtained in the carrageenan processing was evaluated. Considering the variations of productivity during different climatic seasons, three differentiated groups (A, B and C) were defined for each studied strain. The productivity and growth rates were more pronounced in the seasons of summer-autumn (group B). The average productivity of untreated biomass of different strains of K. alvarezii was 31.6 kg.m−2year−1. The average yield of the RC and RE of different strains of K. alvarezii were 14.4 and 7.4 kg.m−2year−1, respectively. RCs showed a galactan enrichment, same as commercial-grade carrageenan. REs showed a glucan enrichment, with average content (A, B and C) of 31.5%, 34.3% and 32.6%, respectively. Enzymatic hydrolysis of the glucan fraction of the RE, resulted in a 100% conversion and indicated that the rate of glucose formation from glucan does not depend on the studied cultures or strains. Therefore, these results show that glucose from RE can be obtained throughout the year, reaching an average productivity of 2.7 kg.m−2year−1.
Keywords: Chemical composition; Cultures; Enzymatic hydrolysis; Kappaphycus alvarezii; Productivity; Refined carrageenan; Residue